Early Lateral Closing Wedge Surgical Correction of Cubitus Varus Deformity Complicating Supracondylar Humeral Fracture in Children (Texas Journal of Medical Science, 2024)
Cubitus varus deformity complicating supracondylar fracture of humerus in children usually implies a malunion from inappropriate treatment of the fracture . The resulting deformity can be solved only by osteotomy ,since the deformity once established it will not correct by remodeling . A lot of controversy is still present regarding the best age of the child to perform the corrective osteotomy . Cosmetic appearance is the most common indication for osteotomy